(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article explores the concept of creative thinking, its significance, and how it can be nurtured in children. It discusses strategies for developing creative thinking skills, provides tips for fostering creativity, and introduces games and activities that enhance children’s creative abilities.